Negotiation in the workplace - Sleeth, Shannon; Collins, Cath; Boland, Michael; Video Education Australasia (Victoria : Video Education Australasia, 2007)
This program explores the fundamentals and intricacies of the negotiation process through a fictional scenario of a high school teacher attemting to organise camp for her basketball team with her travel agent. The program explores the five stages of the negotiation process, including preparation for negotiation, negotiating, bargaining and confirmation
Title from container
Executive producer : Mark McAuliffe ; senior producer : Richard Leigh ; sound : Wayne Martin, Alexy Gudimenko ; camera : Nick Hayward
Voice over : Amy Blackmur
Keywords: Negotiation; Negotiation in business